Grammar and usage, a study in the phenomenon of deletion. Delete the added form.Adel mohamed al najem (Journal of Human Sciences, 2022)
Modern linguistics were interested in the study of language in use, and this approach led to results that necessitated a review of some grammatical phenomena, where it became clear that some linguistic provisions relied on a logic that was not in line with the logic of natural language, and Arabic grammar was not immune to this phenomenon, especially in its post-emergence stages with the early scholars, and the circumstances in which Arabic grammar and the cultural context that prevailed at that stage arose also played a prominent role in the formulation of grammatical theory, On the other hand, linguistic use often encountered these rules, revealing the other side of the language (use), which the rules were unable to limit to its laws, resulting in a discrepancy between rule and use, which was evident in the areas of text analysis in the Arab heritage, in particular the interpretation of the Qur'an in the field of this study. From this point of view, this study came to show an important aspect of the linguistic lesson. The problem of research is illustrated by the following question: to what extent have the grammars in the Arab heritage included rules for use? In other words, has grammar been able to limit use as an inherent part of linguistic circulation? The answer to this question categorically seems difficult because of the distance between the two phenomena, as it was not possible to restrict the use and frame it in specific rules because it is linked to other aspects outside the language,  Furthermore, some rules accept many interpretations. This phenomenon (interpretation), which is linked to the recipient of the language and his competence and not to its producer, was not present in Arabic grammar in a way that would ensure the rules are consistent with usage, and thus limit the process of expanding interpretation and expanding the multiplicity of readings, which is what the theories that were concerned with usage in modern linguistic study revealed.